#### Answer

y = 0

#### Work Step by Step

Solve: 7y + 2 = 6y + 2
7y + 2 = 6y + 2
7y + 2 - 6y = 6y + 2 - 6y
y + 2 = 2
y + 2 - 2 = 2 - 2
y = 0

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

y = 0

Solve: 7y + 2 = 6y + 2
7y + 2 = 6y + 2
7y + 2 - 6y = 6y + 2 - 6y
y + 2 = 2
y + 2 - 2 = 2 - 2
y = 0

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.